1994
DOI: 10.1007/bf00192447
|View full text |Cite
|
Sign up to set email alerts
|

Transfemoral liver biopsy by forceps: A review of 104 consecutive procedures

Abstract: We found transfemoral liver biopsy using forceps to be a safe, well-tolerated procedure with a high diagnostic yield and it is a technically easy alternative to the transjugular approach using large needles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…TJLB with a biopsy forceps is usually a feasible alternative. In addition, several investigators also have reported high safety and efficacy for transfemoral liver biopsy with a biopsy forceps; however, the obtained liver specimens are often suboptimal because of excessive tissue fragmentation and small volumes. Two of our study patients had histories of TJLB with a biopsy forceps, but the obtained liver specimens were suboptimal for histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…TJLB with a biopsy forceps is usually a feasible alternative. In addition, several investigators also have reported high safety and efficacy for transfemoral liver biopsy with a biopsy forceps; however, the obtained liver specimens are often suboptimal because of excessive tissue fragmentation and small volumes. Two of our study patients had histories of TJLB with a biopsy forceps, but the obtained liver specimens were suboptimal for histological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Using standard techniques, the femoral vein, usually that on the right, is punctured and catheterized in order to achieve access to the inferior vena cava. 5 Using a cobra-shaped catheter it is possible to catheterize the hepatic veins, and a venogram is usually obtained in order to demonstrate anatomy. Pressures are obtained within the vena cava, the free hepatic vein, as well as wedged within the hepatic vein to document the degree of portal hypertension.…”
Section: Techniquementioning
confidence: 99%
“…In addition, many patients find use of a transjugular route disagreeable, but tolerate a transfemoral route more readily. 5,6 In the present article we briefly outline our technique for transfemoral venous liver biopsy and illustrate some of the problems and complications we have encountered, with suggestions for subsequent management.…”
Section: Introductionmentioning
confidence: 99%